(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This study investigates the effectiveness of the Communicative Approach in developing speaking skills among EFL learners. Using a mixed-methods design, 60 intermediate-level students were divided into an experimental group, taught through communicative activities, and a control group, taught through traditional methods. Pre- and post-tests, classroom observations, questionnaires, and interviews were employed to collect data. Results revealed that the experimental group demonstrated significant improvement in fluency, vocabulary, pronunciation, accuracy, and overall communicative competence. Qualitative data confirmed increased learner confidence, motivation, and engagement. The findings suggest that the Communicative Approach is highly effective in fostering oral proficiency and creating learner-centered, interactive classrooms.